Implementasi Nilai Pancasila sebagai Dasar Hukum Humanis Terhadap Karakter Bangsa - Ar Rahiim Innash (Universitas Ngudi Waluyo, 2025)
If we observe the existing legal system in Indonesia, there is a foundational legal principle that is deeply rooted in the country, namely Bhinneka Tunggal Ika, which means